Long is the way and hard : one hundred years of the National Association for the Advancement of Colored People (NAACP) - Verney, Kevern, 1960-; Sartain, Lee (University of Arkansas Press, 2009)
Kevern Verney is associate head of the Department of English and History at Edge Hill University, England, and the author of The Debate on Black Civil Rights in America.
Not distributed; available at Arkansas State Library.
Keywords: National Association for the Advancement of Colored People -- History -- 20th century.; National Association for the Advancement of Colored People; African Americans -- Civil rights -- History -- 20th century.; Civil rights movements -- United States -- History -- 20th century.; African Americans -- Politics and government -- 20th century.; United States -- Race relations.; Noirs américains -- Droits -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Politique et gouvernement -- 20e siècle.; États-Unis -- Relations raciales.; HISTORY -- United States -- State & Local -- General.; POLITICAL SCIENCE -- Civil Rights.; African Americans -- Civil rights; African Americans -- Politics and government; Civil rights movements; Race relations; United States; 1900-1999; History